Relative Involvement of Men and Women in Dairying - Anil SS (Department Of Extension, College Of Veterinary And Animal Sciences, 1992)
The objectives of the study were, to assess the extent of physical involvement and involvement in decision-taking by men and women in dairy management practices, to probe into the influence of women in the adoption of practices, to study the extent of adoption of selected aspects in dairying, the reasons for non-adoption/partial adoption of the practices, if any, to study the influence of selected socio-economic factors on adoption and to reveal the knowledge level of men and women about dairy management practices. The study was conducted among the members of the milk producers' co-operative society, Vilanganoor. The data were collected through personal interview using pre-tested interview schedule. Variables were measured using appropriate scales and suitable statistical tools were used for analysing the data. The study revealed that majority of husbands and wives had medium knowledge level. Husbands had significantly higher knowledge than wives in general even though there was no significant difference in the aspects of feeding, milking and breeding. In the aspects of housing and feeding the physical involvement of wives was significantly higher. In all the other aspects husbands' scores were significantly higher except in the case of milking where there was not much difference. In decision-taking, the husbands had significantly higher involvement in all aspects except feeding and milking. It was also noted that the children had important role in these two aspects in few households. There was a high rate of adoption of practices related to the selected aspects in dairying among the respondents (mean adoption index - 86.037). The physical involvement of women in the adoption and their involvement in decision-taking though not significant in general indicate their fairly good influence in the adoption of dairy husbandry practices. The correlation coefficients worked out revealed that out of the 13 socio-economic factors included in the study, only the land holding, experience in dairying, availability of professional help at farmers' premises and occupation had significant association with adoption. Experience in dairying had significant positive correlation with adoption of scientific selection in the case of husbands. Similarly land holding was positively and significantly associated with adoption of scientific housing. Availability of professional help at farmers' premises was significantly and negatively correlated with adoption of scientific housing, while it had highly significant positive correlation with adoption of scientific treatment. Occupation of husbands and adoption of practices in the aspect of feeding were highly significantly and negatively correlated. Occupation had significant negative correlation with adoption of aspects in general in the case of husbands. Since the value of multiple regression analysis was low no further analysis was done. The major constraints faced by farmers in the adoption of scientific practices were lack of money, high cost of feed, repeat breeding and non-availability of medicines.